Preliminary study on antimicrobial activities of skin mucus from by-catch of Elasmobranch species - Aydoğdu Elif Özlem Arslan; Kesiktaş Mert; Sanli Nazmiye Ozlem; Güngör Nihal Doğruöz; Sancar Serap; Yildiz Taner; Yemişken Emre (Oceanological and Hydrobiological Studies)
Skates and rays, which are widely encountered in the by-catch of fisheries activities from the Sea of Marmara and banned for sale by regulation, are species that are discarded if caught. For this reason, in our study, we aimed to determine the bioactive potentials of these species, considered fishing waste, by investigating the skin secretions and microbial flora. In our study, both the skin flora and mucus contents of the discarded species Dasyatis pastinaca (Linnaeus, 1758), Myliobatis aquila (Linnaeus, 1758), and Raja clavata (Linnaeus, 1758) caught in the Sea of Marmara were investigated to determine their potential antimicrobial activities. A total of 164 bacteria were isolated from the epidermal mucus of the three batoid species. Antibacterial activity was observed from three isolated bacteria against Escherichia coli, Vancomycin-resistant Enterococcus faecium, E. faecalis, and Bacillus subtilis. Additionally, the highest antibacterial activity was observed for skin mucus of R. clavata. Mouse fibroblast cell viability was challenged with mucus secretions. M. aquila and R. clavata mucus secretions exhibited no observable change after 24 and 48 hours. The assays indicated that both the isolates and the skin mucus have potential antimicrobial activity against opportunistic pathogens.